Fungsi Pragmatik Permainan Kata pada Wacana Iklan Audiovisual “Santarou” Berbahasa Jepang - Ilham Hijrah Mustaqim; Nani Sunarni; Agus Suherman Suryadimulya (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
Wordplay or paronomasia is a type of verbal humor based on the ambiguity between two similar-sounding words or one word with multiple meanings. Wordplay is known for being used in advertisement, but it is still unclear what specific function it has in realizing the communicative purpose of the text, especially in regard to pragmatic function, that is, whether the text is informative, appellative, commissive, or contactive. This research aims to analyze how wordplay is used in the Japanese-language audiovisual advertisement titled “Santarou” and identify its pragmatic functions. It is qualitative research using the observation method for data collection and the identity method for data analysis. The results indicate that wordplay could be used to indirectly discuss the product being offered with ambiguous utterances in the case of informative and appellative advertisements, to connect the situation depicted in the advertisement with the product in the case of commissive advertisement, and to attract the audience’s attention and associate a characteristic with the brand in the case of contact advertisement.